Role of Gut Microbiota in Pulmonary Arterial Hypertension - Wu, Panyun; Zhu, Tengteng; Tan, Zhen; Chen, Shenglan; Fang, Zhenfei (Frontiers in Cellular and Infection Microbiology, 2022)
Gut microbiota and its metabolites play an important role in maintaining host homeostasis. Pulmonary arterial hypertension (PAH) is a malignant clinical syndrome with a frightening mortality. Pulmonary vascular remodeling is an important feature of PAH, and its pathogenesis is not well established. With the progress of studies on intestinal microbes in different disease, cumulative evidence indicates that gut microbiota plays a major role in PAH pathophysiology. In this review, we will systematically summarize translational and preclinical data on the correlation between gut dysbiosis and PAH and investigate the role of gut dysbiosis in the causation of PAH. Then, we point out the potential significance of gut dysbiosis in the diagnosis and treatment of PAH as well as several problems that remain to be resolved in the field of gut dysbiosis and PAH. All of this knowledge of gut microbiome might pave the way for the extension of novel pathophysiological mechanisms, diagnosis, and targeted therapies for PAH.